Circulating lncRNAs NONHSAT054669.2 and ENST00000525337 can be used as early biomarkers of gestational diabetes mellitus. Issue 6 (March 2023) - Jiang, Wen; Sun, Xiubin; Liu, Fangfei; Cheng, Guanghui; Li, Siyuan; Xu, Mengru; Wu, Yu; Wang, Lina
Early diagnosis can help prevent and reduce the adverse effects of gestational diabetes mellitus (GDM). This study intended to investigate key circulating long non-coding RNAs (lncRNAs) as novel biomarkers for diagnosis of GDM at the early stages. First, lncRNA microarray analysis was conducted for plasma samples of GDM women before delivery and 48 h after delivery. The expression of differentially expressed lncRNAs in clinical samples at different trimesters was randomly validated by quantitative polymerase chain reaction (PCR). Moreover, the correlation between lncRNA expression and oral glucose tolerance test (OGTT) level in GDM women during the second trimester was analyzed, followed by evaluating the diagnostic value of key lncRNAs during different trimesters using receiver operating characteristic (ROC) curve. Higher NONHSAT054669.2 expression and lower ENST00000525337 expression were revealed in GDM women before delivery relative to 48 h after delivery ( P  < 0.05). The expression of NONHSAT054669.2 and ENST00000525337 in GDM women during the first and second trimesters was dramatically higher than pregnant women ( P  < 0.05) with normal glucose tolerance (NGT). During the second trimester, NONHSAT054669.2 expression was positively related to OGTT level at 1 h ( r  = 0.41455, P  < 0.001). Furthermore, ROC curve analysis revealed that ENST00000525337 alone, NONHSAT054669.2 alone, and their combination had high diagnostic value for GDM during the first (area under the ROC curve (AUC) = 0.979, 0.956, and 0.984, respectively) and second (AUC = 0.829, 0.809, and 0.838, respectively) trimesters (all P  < 0.001). The plasma level of NONHSAT054669.2 and ENST00000525337 may be applied as novel diagnostic biomarkers for early diagnosis of GDM.